2004
DOI: 10.1128/iai.72.10.5630-5637.2004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of the Proinflammatory Cytokines Interleukin-1 Beta (IL-1β), IL-6, IL-8, IL-10, Tumor Necrosis Factor Alpha, and IL-12(p70) in Malian Children with SeverePlasmodium falciparumMalaria and Matched Uncomplicated Malaria or Healthy Controls

Abstract: Inflammatory cytokines play an important role in human immune responses to malarial disease. However, the role of these mediators in disease pathogenesis, and the relationship between host protection and injury remains unclear. A total of 248 cases of severe Plasmodium falciparum malaria among children aged 3 months to 14 years residing in Bandiagara, Mali, were matched to cases of uncomplicated malaria and healthy controls. Using modified World Health Organization criteria for defining severe malaria, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
364
5
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(408 citation statements)
references
References 47 publications
31
364
5
8
Order By: Relevance
“…Although IL-23 and IL-12 share the p40 subunit [17], levels of IL-23 were elevated in children with malarial anemia, while plasma IL-12 concentrations progressively declined with increasing anemia severity. The decrease in IL-12 with increasing disease severity parallels previous findings in African children residing in areas with intense malaria transmission [12][13][14]29,[43][44][45]. In addition, examination of the IL-12 to IL-23 ratio revealed that SMA is characterized by low levels of IL-12 relative to IL-23.…”
Section: Discussionsupporting
confidence: 82%
“…Although IL-23 and IL-12 share the p40 subunit [17], levels of IL-23 were elevated in children with malarial anemia, while plasma IL-12 concentrations progressively declined with increasing anemia severity. The decrease in IL-12 with increasing disease severity parallels previous findings in African children residing in areas with intense malaria transmission [12][13][14]29,[43][44][45]. In addition, examination of the IL-12 to IL-23 ratio revealed that SMA is characterized by low levels of IL-12 relative to IL-23.…”
Section: Discussionsupporting
confidence: 82%
“…A predominantly proinflammatory response was associated with more rapid control of parasite growth but only at the cost of developing clinical symptoms. These observations strongly support the conclusions of several correlative clinical and epidemiological studies that have also suggested that proinflammatory responses might be causally associated with both clearance of parasites and clinical disease (14,22,33). Conversely, subjects in group 3 who had no detectable inflammatory response but the highest levels of TGF-␤ were less able to control parasite growth (30) but hardly ever reported a fever or feverishness, again supporting data from studies in malaria endemic populations that anti-inflammatory activity is associated with less severe clinical symptoms (22).…”
Section: Discussionsupporting
confidence: 78%
“…IFN-␥ is the key inducer of the immune effector mechanisms that are essential for initial control of both pre-erythrocytic and blood-stage malaria infections (8,9), but there is evidence that IFN-␥ levels need to be carefully balanced to avoid immune pathology (10,11). In vivo, TNF-␣ production is associated with parasite clearance and resolution of fever (12), but elevated levels of TNF-␣ (13) and IL-6 (14,15) have also been associated with cerebral malaria. A priori, one would expect a crucial role for IL-12-and possibly also IL-18 -in initiation of the inflammatory cytokine cascade.…”
Section: R Esearch On the Immunology Of Malaria Infection Has Beenmentioning
confidence: 99%
“…The cascade of cytokines released during the erythrocytic stages of infection, particularly pyrogenic cytokines such as TNF‐ α , IL‐1 β and IL‐6,5, 60, 82, 83, 84, 85 cause acute inflammation, which mediates immunopathology 4, 5, 60, 86, 87, 88. These cytokines are necessary for several antiparasitic effector processes, such as skewing the T‐cell response to a more pronounced T helper type 1 (Th1) response during infection,89, 90 directly killing or inhibiting parasite growth, as has been observed for TNF‐ α and IFN‐ γ, 91 and indirectly killing parasites by activating phagocytic cells 85, 91.…”
Section: The Role Of Inflammation In Malarial Pathogenesismentioning
confidence: 99%